Evaluación de los parámetros zootécnicos de interés en la producción de cuyes (cavia porcellus) del ceasa para perfeccionar el programa de mejoramiento genético. - Iza Quispe, Esthela Judith (2020)
The guinea pig (Cavia porcellus) is one of the species most related to the life and tradition of indigenous society; and originated in the countries of Colombia, Ecuador, Peru and Bolivia, these animals are very important due to the role they play in rural families in Ecuador and the nutritional value they provide. This research project was carried out in the province of Cotopaxi, Latacunga canton, Eloy Alfaro parish at the Technical University of Cotopaxi, at the Salache Experimental and Academic Center (CEASA) and it is part of the Guinea Pig Genetic Improvement Project. The objective of the research project is to evaluate the zootechnical parameters of interest in the production of guinea pigs (Cavia porcellus). We worked with the total population of the campus that consists of 247 guinea pigs between males and females, began with the identification and phenotypic characterization of each animal, both productive and reproductive. Subsequently, the daily weight gain (gdp) and the prolificity that are widely used parameters in the programs of genetic selection and economic importance were recorded since they directly affect the profitability of the campus, the daily gain is an indicator of good use and use of the animal resource, obtaining animals that reach term in the shortest possible time reducing production costs and in terms of prolificacy, because the reproductive life of the guinea pig is short approximately 2 years, this parameter should be maximized because increasing the number of guinea pigs sold per mother per year will generate more income and increase the number of guinea pigs to replace the same population. The determination of the daily weight gains allowed to detect low levels in the breeding and breeding categories, however, there is superiority of the category rabbits, in terms of sex it was shown that males gain more weight than females, the composite color positively influences in the daily weight gain and the Peru, Andean line, they are the ones that gain the most weight compared to the inti. The prolificity of the CEASA campus is 2.17 offspring / childbirth which is low and has an economic impact on the campus. Finally, a mass selection was made for the mentioned characters and the genetic value of the animals selected for each of the characters of interest was estimated from the pedigree information, obtaining a total number of 35 animals of the 3 categories that exceed the average of gdp of the total population, thus forming the nucleus of daily weight gain and 2 prolific breeding females were selected forming the nucleus of prolificity. All this research project is aimed at improving productivity in the raising of guinea pigs and therefore the economy and the standard of living of the producers.